Implementation of the Simple Additive Weighting (SAW) Method in the Selection of Recipients of Social Funds for Poor Families - Muhammad Tri Vaneza; Mesran Mesran; Joli Afriany; Wily Julitawaty; Kelik Sussolaikah (The IJICS (International Journal of Informatics and Computer Science), 2021)
Decision support system is the implementation of several decision-making theories by sciences such as operations research and management science. There are several differences, namely if in the past to find a solution to the problem at hand, iteration calculations had to be done manually or usually looked for the minimum, maximum, and optimum values, now Pc computers have offered the ability to solve the same problems in a relatively short time. In this study using the Simple Additive Weighting (SAW) method for collecting data on receipts of social assistance funds for poor families carried out by PT. Bank Negara Indonesia (Persero) Tbk. become more systematic and the right of recipients of social assistance funds is right for the people in need